SANKSI ADAT BAGI PELAKU MEKHOBA DI KECAMATAN GUNUNG MERIAH ACEH SINGKIL - Khairuddin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2019)
Mekhoba is a form of marriage proposal in Aceh Singkil. However, this application has customs and laws that must be resolved after the mekhoba. After notification that someone's daughter has been escorted to the village head or priest's place, then the family of the woman must not bring the daughter before this problem is resolved in adat and law. Adat they want to get married and their laws must be married. After the child is brought to the place of the priest, then from the man's side he will pay a penitent money / lose a woman because it has been brought by a man, this will be subject to customary sanctions, namely first, paying money of five hundred thousand rupiahs, or more, as requested by the women, secondly, they will be married off as soon as possible, because if it is feared that they will not get married, thirdly, they will pay for food for women who are entrusted to the village office such as the village head or priest.